Indications and results in anophthalmic socket reconstruction using dermis-fat graft - Aryasit O (Dove Medical Press, 2015)
Orapan Aryasit, Passorn Preechawai Department of Ophthalmology, Faculty of Medicine, Prince of Songkla University, Hat Yai, Songkhla, Thailand Objectives: To present the indications for a dermis-fat graft in anophthalmic socket reconstruction and evaluate the results of this procedure.Design: Retrospective review, interventional case series.Methods: In our study, there were 41 patients who received either primary or secondary dermis-fat graft between August 1, 2007 and July 31, 2012 at Songklanagarind Hospital.Results: The type of dermis-fat graft used in our study consisted of both primary dermis-fat grafts (6/41) and secondary dermis-fat grafts (35/41). The major indications for dermis-fat graft were exposure (13/41), extrusion (11/41), and volume insufficiency with a shallow fornix (10/41), which accounted for 82.9% of the total cases. A total of 30 patients were able to wear the eye prosthesis over a mean follow-up time of 32.3±19.0 months. The success rate of the dermis-fat graft alone was 73.3%, while that of the simultaneous dermis-fat graft and mucous-membrane graft was 25%.Conclusion: The most common indications for a dermis-fat graft were extrusion and large exposure. Dermis-fat graft is an alternative implant type in complicated enucleation/evisceration patients, which has a good success rate. Keywords: dermis-fat graft, anophthalmic socket, extrusion, exposure